Comprehensive approaches to suicide prevention in undergraduate students: A scoping review of psychological, social, and institutional strategies - Yuniar Mansye Soeli; Novy Helena Catharina Daulima; Mustikasari Mustikasari; Evi Martha (Jurnal Keperawatan Padjadjaran, 2025)
Background: Suicide represents a significant mental health issue worldwide, particularly among undergraduate students, and is intensified by various psychological, social, and institutional stressors. Despite heightened awareness of the problem, existing prevention strategies frequently concentrate on discrete interventions while overlooking broader systemic and societal factors that influence student well-being. Objective: This scoping review seeks to investigate current suicide prevention methods aimed at undergraduate students by organizing these strategies into three main domains: psychological, social, and institutional. Methods: The research adhered to Arksey and O’Malley’s (2005) framework for scoping reviews as well as PRISMA-ScR guidelines. A comprehensive search was performed across numerous databases—such as PubMed, ScienceDirect, ProQuest, and Google Scholar—for studies published between 2010 and 2024. The inclusion criteria targeted interventions specifically designed for undergraduate populations utilizing either psychological or social approaches within an institutional context. Thematic synthesis facilitated the categorization of intervention types while descriptive statistics provided a summary of study characteristics. Results: Seventeen studies were included in this review that assessed suicide prevention initiatives across different levels. Psychological approaches like cognitive-behavioral therapy (CBT), digital mental health resources, along with peer support programs demonstrated considerable effectiveness in reducing suicide risk and improving overall mental wellness. Social elements such as family involvement，cultural sensitivity，and community-based programs were identified as vital contributors to emotional resilience enhancement. Institutional measures—including gatekeeper training sessions，crisis response policies，and adaptable academic accommodations were highlighted as essential components necessary for fostering supportive environments within universities. Importantly，“digital”mental health solutions are gaining traction; although they present scalable opportunities for improvement. Conclusion: The study emphasizes the need for a comprehensive approach to suicide prevention in university settings, involving psychological, social, and institutional strategies. Future efforts should focus on building digital-human hybrid models that strengthen early detection and empathetic engagement.